Efficacy of Continuous Performance Testing in Adult ADHD in a Clinical Sample Using QbTest+. Issue 11 (September 2022) - Adamou, Marios; Jones, Sarah L.; Marks, Laura; Lowe, Deborah
Objective: Continuous performance tests are widely used to aid diagnostic decision making and measure symptom reduction in adult ADHD clinical populations. The diagnostic accuracy of the Quantified Behavior Test plus (QbTest+), developed to identify ADHD populations as an objective measure of ADHD symptoms, was explored. Methods: The utility of the QbTest+ was investigated in a clinical cohort of 69 adult patients referred to a specialist ADHD clinic in the UK. Results: Scores from the QbTest+ failed to differentiate between patients diagnosed with ADHD and those who did not receive a diagnosis after full clinical assessment. Conclusions: Based on our findings, we recommend clinicians are cautious when interpreting results of the QbTest+ in clinical populations. This study highlights the need for investigation into the lack of validation of commonly used objective measures in ADHD populations.